Pemetaan Kerentanan Gerakan Tanah dan Batuan Desa Hargorejo dan Sekitarnya, Kecamatan Kokap, Kabupaten Kulon Progo, Propinsi Daerah Istimewa Yogyakarta - SETIYANTO, Adhy ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Movement soil and rocks including natural disasters that are often in parts of Indonesia. Research on the vulnerability of soil and rock movement is needed in the area of Hargorejo village, Kokap district, regency of Kulon Progo considering that area is an area that is vulnerable to movement of soil and rock. The purpose of this study was to: 1) Know the types of soil and rock movement of the study area, 2) Knowing the dominant controlling factor which can cause soil and rock movements occur in the study area, 3) Create a map of vulnerability movement of soil and rocks in the study area. The method use in this study includes geological mapping, then the specified parameters that are controlling for vulnerability of movement soil and rocks are: slope, lithology, geological structure, surface soil types, and land use. From parameters, made maps based on these parameters for later in the overlay using Geographic Information Systems (GIS) produces map of vulnerability soil and rocks movement . The conclusion of this study find that: 1) The movement of soil and rocks are dominant in the study area in the form of creep and slide, 2) The most influential parameter until not too powerful are lithology, geological structure, slope, surface soil types, and land use, 3) There are 3 zones vulnerable of movement soil and rocks. Vulnerability of high level zones are Hargorejo village, Tangkisan Dua, and Ngaseman. Vulnerability of medium level zones are Kulur village and Tangkisan Satu. Vulnerability of low-level zones is Temon Kulon village.